2018
DOI: 10.26603/ijspt20180561
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Patient Demographics and Graft Types on Acl Second Injury Rates in Ipsilateral Versus Contralateral Knees: A Systematic Review and Meta-Analysis

Abstract: Background: There are inconsistencies in the reported rates of second anterior cruciate ligament (ACL) injuries per limb, patients' sex and graft types after primary ACL reconstruction (ACLR). There are also inconsistencies regarding the influence of these factors on the occurrence of second ACL injury after primary ACLR. Purpose:To determine the rate of second ACL injury, to either the ipsilateral graft or contralateral healthy ACL, as influenced by sex, age, and graft types and to determine the influence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 85 publications
0
18
1
1
Order By: Relevance
“…This finding is similar to that in a recent systematic review of smaller studies that reported lower rates of ipsilateral graft ruptures in women. 25 This review also found that women had a higher rate of contralateral knee injuries; however, in our study, we found no difference in contralateral ACL reconstruction rates in women versus men. Subsequent meniscal surgery rates were also lower in women than men.…”
Section: Discussioncontrasting
confidence: 62%
“…This finding is similar to that in a recent systematic review of smaller studies that reported lower rates of ipsilateral graft ruptures in women. 25 This review also found that women had a higher rate of contralateral knee injuries; however, in our study, we found no difference in contralateral ACL reconstruction rates in women versus men. Subsequent meniscal surgery rates were also lower in women than men.…”
Section: Discussioncontrasting
confidence: 62%
“…Males and females were found to be equally likely to experience a second ACL injury. Although a previous meta-analysis reported that females have higher odds of experiencing a second ACL injury than males, 70 this discrepancy is likely due to the absence of considering return-to-sport percentage in their inclusion criteria. This suggests that their findings might better reflect general populace ACL injury trends.…”
Section: Risk Of a Second Acl Injurymentioning
confidence: 91%
“…1 Unfortunately, a rupture of the reconstructed ACL, an ACL re-rupture, can occur and is regarded as definite treatment failure. Re-ruptures of the ACL occur a median of 20 months after primary reconstruction and the rates typically vary between 3 and 7%, 2,3 but they can be as high as 10% in younger athletes. 3 In addition, re-ruptures have an increased presence of cartilage injuries compared with primary ACL injuries.…”
Section: Introductionmentioning
confidence: 99%